Hematita: um novo método de síntese para a indústria - Costa, Célia Domingues da (2011)
The motivation in studying the properties of iron oxides was due to difficulty in obtaining colored pencils in shades of brown, with good coverage. To carry out this work we used pigments for industrial use Icra provided by the company that is seeking new technologies to modernize its industrial park and the company Faber-Castell new suppliers of pigments. To study the pigment supplier of business best suited to the project was used atritor grinding mill, to assess the behavior of the pigment in high-energy milling and after analysis of the pigments was selected the most suitable for continuation of the project. Developed methodology to improve the physical and chemical characteristics of the pigment in different processing times by microwave hydrothermal. These techniques allowed to evaluate the evolution of the phases, morphology and structural disorder in samples of atritor milling and recrystallization of the pigment using the microwave hydrothermal. The characterization techniques used in the project were: BET, X-ray diffraction (XRD), Raman spectroscopy, infrared spectroscopy, absorption spectroscopy in the ultraviolet-visible (UV-vis), scanning electron microscopy with field emission (FEG-SEM).